Arabidopsis thaliana as a tool to identify traits involved in Verticillium dahliae biocontrol by the olive root endophyte Pseudomonas fluorescens PICF7 - Maldonado-González, M. Mercedes; Bakker, Peter A. H. M.; Prieto, Pilar; Mercado-Blanco, Jesús (Frontiers in Microbiology, 2015)
The effective management of Verticillium wilts (VW), diseases affecting many crops and caused by some species of the soil-borne fungus Verticillium, is problematic. The use of microbial antagonists to control these pathologies fits modern sustainable agriculture criteria. Pseudomonas fluorescens PICF7 is an endophytic bacterium isolated from olive roots with demonstrated ability to control VW of olive caused by the highly virulent, defoliating (D) pathotype of Verticillium dahliae Kleb. However, the study of the PICF7-V. dahliae-olive tripartite interaction poses difficulties because of the inherent characteristics of woody, long-living plants. To overcome these problems we explored the use of the model plant Arabidopsis thaliana. Results obtained in this study showed that: (i) olive D and non-defoliating V. dahliae pathotypes produce differential disease severity in A. thaliana plants; (ii) strain PICF7 is able to colonize and persist in the A. thaliana rhizosphere but is not endophytic in Arabidopsis; and (iii) strain PICF7 controls VW in Arabidopsis. Additionally, as previously observed in olive, neither swimming motility nor siderophore production by PICF7 are required for VW control in A. thaliana, whilst cysteine auxotrophy decreased the effectiveness of PICF7. Moreover, when applied to the roots PICF7 controlled Botrytis cinerea infection in the leaves of Arabidopsis, suggesting that this strain is able to induce systemic resistance. A. thaliana is therefore a suitable alternative to olive bioassays to unravel biocontrol traits involved in biological control of V. dahliae by P. fluorescens PICF7.